2001
DOI: 10.1097/00000374-200112000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Related Impact of Alcohol Consumption on Cognitive Function in Advanced Age: Results of a Multicenter Survey

Abstract: Alcohol abuse is associated with increased prevalence of cognitive dysfunction among older subjects; however, a daily alcohol consumption of less than 40 g for women and 80 g or less for men might be associated with a decreased probability of cognitive impairment. This possible protective effect of alcohol consumption should be further assessed by prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 32 publications
4
38
1
1
Order By: Relevance
“…Other studies also detected sex differences [106,107,111]. Light to moderate alcohol consumption was also found beneficial based on findings of other cohort and cross-sectional studies with a U- or J-shaped pattern observed [108-110,113,114,116,117,119-121,124-127]. However, in other studies, a linear dose–response relationship between alcohol use and improved cognition was noted, though the authors cautioned that these should not encourage increased alcohol consumption without an upper bound to this consumption [114,115,122,131].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Other studies also detected sex differences [106,107,111]. Light to moderate alcohol consumption was also found beneficial based on findings of other cohort and cross-sectional studies with a U- or J-shaped pattern observed [108-110,113,114,116,117,119-121,124-127]. However, in other studies, a linear dose–response relationship between alcohol use and improved cognition was noted, though the authors cautioned that these should not encourage increased alcohol consumption without an upper bound to this consumption [114,115,122,131].…”
Section: Resultsmentioning
confidence: 88%
“…9 of the 12 cross-sectional studies (75%) found an association in the hypothesized direction for the entire study population and for most outcomes of interest [106,109,110,119,121,123,126-128]. The remaining 3 studies either found this U-shaped or J-shaped association in a sub-group [107], and either failed to detect any association [112] or detected one that was not in line with the hypothesis, whereby alcohol use was generally found to result in poor cognitive outcomes [130].…”
Section: Resultsmentioning
confidence: 99%
“…Age or disease-related changes in major organs (12) can decrease alcohol tolerance, metabolism, distribution, and elimination leading to adverse alcohol-related consequences at lower levels of consumption (13). Common alcohol-related consequences among older adults include falls, memory problems, and adverse alcohol–prescription drug interactions requiring emergency medical attention and/or hospitalization (10,12,14). Interactions between alcohol and prescription drugs, especially those prescribed for diabetes, hypertension, anxiety, and depression, can alter medication effectiveness, lead to misdiagnosis, and result in life-threatening medical complications (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between alcohol and prescription drugs, especially those prescribed for diabetes, hypertension, anxiety, and depression, can alter medication effectiveness, lead to misdiagnosis, and result in life-threatening medical complications (10,12). Risky drinking among older adults may contribute to declines in cognition, slowed reaction times, and changes in spatial perception and balance—all posing dangers for older adults who drive or live alone (14). …”
Section: Introductionmentioning
confidence: 99%
“…Some reasons for the differences among studies include length of follow-up, how alcohol use is defined, which cognitive measures are used, sociodemographics and under- or over-adjustment for confounders. Some studies have shown that alcohol use is associated with either increased cognitive impairment 21 or decreased cognitive impairment 22 . Other studies have shown that current alcohol users have better cognitive performance than former alcohol users or those who have never used alcohol 2328 .…”
Section: Introductionmentioning
confidence: 99%